Representations of the Coronavirus in English Discourse - 이혜경; 이선희 (담화와 인지, 2023)
The presence and spread of the COVID-19 virus continues to afflict people around the world and stoke apprehension and fear in their minds, with a plethora of (mis)information being accumulated. This paper is an attempt to contribute to the research on our perception of the COVID-19 pandemic by investigating how the coronavirus is represented in English texts all around the globe. Utilizing the Coronavirus Corpus as research data, this paper presents that the coronavirus is frequently envisaged to be contracted or spread by common people. At the same, the coronavirus is portrayed to be fought against or defeated by public or collective entities such as governments, nations, societies, or the whole world. It is speculated that this discrepancy may stem from an underlying ideology that authorities or collective entities are empowered to “battle” the virus and win the “war” against it, while ordinary people are actually at the forefront of suffering from evil influences of the virus.
Keywords: the Coronavirus Corpus; corpus-based discourse analysis; COVID-19; representations